Human Rights Discourse for Marginalized People: A Hadith Approach with Hassan Hanafi's Hermeneutics: Diskursus Hak Asasi Manusia untuk Kaum Marginal: Pendekatan Hadis dengan Hermeneutika Hassan Hanafi - Ainul Azhari (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Human rights apply universally regardless of age, religion, gender, nationality, social status, political views, or local language. However, in practice, intolerant behavior is still widely found. This then gave birth to the term marginalized, such as religious minorities, the weak, powerless, poor, and suburban communities. Departing from these problems, it is important to re-read the hadith guidance to determine tolerant, humanist, and respectful attitudes towards others within the framework of human rights. Two questions become the initial basis of the study; first, how does the hadith view marginalized people? Second, how does Hassan Hanafi’s Hermeneutics interpret the hadith on human rights? Both questions were then analyzed using a qualitative approach with descriptive-analysis-based library research and content analysis as a data analysis technique. The results of this study show that Hassan Hanafi’s hermeneutic reading of the hadith termed the value of equality as “being”, with elements such as brotherhood, equality, and humanity included in “being with others”. In addition, safeguarding and fulfilling human rights for marginalized groups, such as the right to life, justice, equality, property, religious freedom, and decent wages, is part of the “being in the world” referred to in the hadith. This is corroborated by the awareness of the Prophet Muhammad, who always provided examples and guidance in upholding and protecting human rights, especially for marginalized groups.